Correlation Red Blood Inidces to Hemogloblin Levels In Addolescent At SMK-TI High School, Badung, Bali - Endrawati Juwita Komang; Ginitri Bulan Anak Agung; Andika Jaya Komang (Al Makki Publisher, 2025)
The Complete Blood Count (CBC) or hemogram is a panel of test results on the cellular components of blood: the Red Blood Cells (RBCS), White Blood Cells (WBCS), and platelets (PLTS). Each of the portions can be interpreted separately in a methodical fashion and the interpretation has two aims for laboratorians. parameter that is quite sensitive to testing errors and interferences (often flagged) is the Mean Cell Hemoglobin Concentration (MCHC). The purpose of checking Hemoglobin levels is to assess the level of anemia, response to anemia therapy, or the development of diseases related to anemia and polycythemia. Other uses for checking Hemoglobin include assessing the level of anemia, the response to anemic women and the development of diseases related to anemia. This research used a crosssectional analytic method with the aim of finding a correlation red blood indices to Hemoglobin. Teenagers are the most prominent investors and the next generation of the nation's ideals. However, in adolescence, many problems can have a negative impact on health, such as adolescent nutrition. The quality and quantity of nutritional intake consumed during adolescence is an important factor in the emergence of nutritional problems in adolescents.